The Effect of Duolingo Usage Duration on Vocabulary Size: A Quasi-Experimental Study at Senior High School NU Palangka Raya - Muhamad Ario Setiawan; Sabarun Sabarun; Zaitun Qamariah (International Journal Labs, 2026)
Vocabulary size is a key component of English as a Foreign Language (EFL) learners’ proficiency; however, many students still struggle to develop sufficient vocabulary, especially in contexts with limited exposure to English. Although previous studies have highlighted the benefits of Mobile-Assisted Language Learning (MALL), the role of structured session duration in vocabulary development remains underexplored. This study examines the effect of fixed Duolingo usage duration on the vocabulary size of twelfth-grade students at SMA NU Palangka Raya. A quasi-experimental design was applied, involving an experimental group and a control group, both receiving pre-tests and post-tests using a standardized vocabulary test. The experimental group completed four 30-miNUte Duolingo sessions, while the control group engaged in conventional instruction, including flashcard memorization and fill-in-the-gap exercises, within the same time allocation. Results indicated improvement in both groups; however, the experimental group achieved significantly higher gains, with a post-test mean score of 66.83 compared to 50.73 in the control group. Statistical analysis revealed a significant difference (t (21) = -5.637, p < .001), demonstrating the effectiveness of structured Duolingo usage. These findings suggest that fixed, time-structured learning supported by adaptive digital features can enhance vocabulary development more effectively than conventional methods. The study underscores the potential of integrating structured mobile learning into classroom practice, although its small sample size and short duration limit generalizability. Further research is needed to examine long-term effects and varied duration designs.